Genetic Diversity of Mycobacterium tuberculosis Complex Isolated from Tuberculosis Patients in Bahir Dar City and Its Surroundings, Northwest Ethiopia. (28th September 2015) - Nuru, Anwar; Mamo, Gezahegne; Worku, Adane; Admasu, Aschalew; Medhin, Girmay; Pieper, Rembert; Ameni, Gobena
Abstract : The knowledge of the diversity of strains of Mycobacterium tuberculosis complex (MTBC) species in a specific geographical region can contribute to the control of tuberculosis (TB). This study was conducted to identify the MTBC isolates to the species and spoligotype international type (SIT) level by spoligotyping. A total of 168 MTBC isolates were recovered from TB patients, spoligotyped, and their patterns were compared with those of the strains registered in the SITVIT2 database. Of 168 isolates spoligotyped, 89 patterns were identified. Ninety-eight isolates were clustered into 19 strain groups with clustering percentage of 58.3%. Forty-four strains matched the preexisting SITs in the SITVIT2 database. The dominant strains were SIT289, SIT134, and SIT3411, comprising 16.7% (28/168), 7.14% (12/168), and 4.76% (8/168) of the isolates, respectively. Euro-American (51.2%), East-African-Indian (34.5%), and M. africanum (9.52%) were the major lineages identified. Two strains of M. bovis were isolated from TB lymphadenitis cases. The high percentage of clustered strains of M. tuberculosis could suggest that a small number of lineages of M. tuberculosis are causing the disease in the area while isolation of M. bovis could suggest its zoonotic potential. Additionally, identification of M. africanum requires further confirmation by tools with a better discriminatory power.